The conflict of principles and the fallacies of freedom (Revista do Tribunal Regional Federal da 3ª Região, 2011)
The text is about the principles of freedom, equality and solidarity and the juridical mistakes about them in a capitalist society.
Keywords: freedom; equality; solidarity